Galaxy disc central surface brightness distribution in the optical and near-infrared bands. Issue 2 (19th January 2019) - Zhou, L; Du, W; Wu, H; Liang, Y C; He, M; Zhao, P S; Deng, L C; Shi, W B; Wang, Y H
Abstract: To study the disc central surface brightness (μ0 ) distribution in optical and near-infrared bands, we select 708 disc-dominated galaxies within a fixed distance of 57 Mpc from SDSS DR7 and UKIDSS DR10. Then we fit μ0 distribution by using single and double Gaussian profiles with an optimal bin size for the final sample of 538 galaxies in optical griz bands and near-infrared YJHK bands. Among the eight bands, we find that μ0 distribution in optical bands cannot be much better fitted with double Gaussian profiles. However, for all the near-infrared bands, the evidence of being better fitted by using double Gaussian profiles is positive. Especially for K band, the evidence of a double Gaussian profile being better than a single Gaussian profile for μ0 distribution is very strong, the reliability of which can be approved by 1000 times test for our sample. No dust extinction correction is applied. The difference of μ0 distribution between optical and near-infrared bands could be caused by the effect of dust extinction in optical bands. Due to the sample selection criteria, our sample is not absolutely complete. However, the sample incompleteness does not change the double Gaussian distribution of μ0 in K band. Furthermore, we discuss some possible reasons for the fitting results of μ0 distribution in K band. Conclusively, the double Gaussian distribution of μ0 in K band for our sample may depend on bulge-to-disc ratio, colour and disc scale length, rather than the inclination of sample galaxies, bin size, and statistical fluctuations.